2012
DOI: 10.1007/s00401-012-0944-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent retroviral infection with MoMuLV influences neuropathological signature and phenotype of prion disease

Abstract: A fundamental step in pathophysiology of prion diseases is the conversion of the host encoded prion protein (PrP(C)) into a misfolded isoform (PrP(Sc)) that accumulates mainly in neuronal but also non-neuronal tissues. Prion diseases are transmissible within and between species. In a subset of prion diseases, peripheral prion uptake and subsequent transport to the central nervous system are key to disease initiation. The involvement of retroviruses in this process has been postulated based on the findings that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
(107 reference statements)
1
18
0
Order By: Relevance
“…Again, we could not detect differences between animals infected with prions vs. those infected with prions + virus (Figure D). As previously reported, the clinical presentation of the prion disease of mice after intraperitoneal prion injection changes upon an additional retrovirus infection . However, changes were less pronounced in the intracerebrally infected when compared with intraperitoneally prion infected mice (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…Again, we could not detect differences between animals infected with prions vs. those infected with prions + virus (Figure D). As previously reported, the clinical presentation of the prion disease of mice after intraperitoneal prion injection changes upon an additional retrovirus infection . However, changes were less pronounced in the intracerebrally infected when compared with intraperitoneally prion infected mice (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…Previously, we showed that persistent retroviral infection with Moloney murine leukemia retrovirus (MoMuLV) changed the neuropathological signature and phenotype of prion disease (Krasemann et al, 2012). In this study, a subset of mice were used that developed spleenomegaly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All procedures involving animals were performed in accordance with the institutional guidelines from the animal facility of the University Medical Center Hamburg-Eppendorf and were in compliance with the Guide for the Care and Use of Laboratory Animals. Mice were inoculated with MoMuLV on post-natal day 5 with~7610 4 IU to achieve virus persistence (Krasemann et al, 2012;Rodenburg et al, 2007;Schwieger et al, 2002). For prion-only infection or infection with both pathogens (MoMuLV+prion), strain RML 5.0 prions (Prinz et al, 2003b) were injected on day 21.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies showed a link between release of retrovirus particles, presence of PrP Sc , and prion infectivity on both, exosomes and retroviral particles, thus it was proposed that retroviral infection could be a cofactor in the spreading of prion disease (Alais et al, 2012). However, subsequent in vivo studies by our group and others did not provide evidence for this, but rather showed that subclinical retroviral infection acts as a disease modifier, but does not enhance spreading of the disease (Alais et al, 2012; Krasemann et al, 2012; Muth et al, 2016). …”
Section: Exosomal Prp In the Pathophysiology Of Prion Disease: Spreadmentioning
confidence: 94%